Analysis of The Effectiveness of Integrated Customer Relationship Management Strategy Implementation on Loyalty of National Logistics Company Customers - Sudirjo, Frans; Kushariyadi; Mustafa, Fahrina; Osman, Isnawati; Henri Kusnadi, Iwan (Jurnal Informasi dan Teknologi, 2024)
This research aims to determine how the IDIC model of customer relationship management strategy is implemented to create brand loyalty. This research uses post-positivism. This research uses a qualitative and descriptive approach. This research method uses the case-study method. The data collection technique in this research is interviewing. This research uses construct validity. The relevant technique for analyzing data in this research is pattern matching. From the results of the research conducted, it was found that the company had succeeded in implementing an effective customer relationship management (CRM) strategy to create brand loyalty. The company also successfully implemented the IDIC model concept in its CRM strategy, which includes identifying customers, differentiating services based on needs, interacting intensively, and adapting services to customer needs through technology. Apart from that, this company has also succeeded in measuring the effectiveness of its CRM strategy through the Net Promoter Score. Furthermore, this research shows that, in contrast to other sectors, B2B logistics companies emphasize service quality and company value more than providing discounts or promotions to increase customer loyalty. As a result, this company gained customer loyalty, which is reflected in its success in extending contracts with its customers.